2010
DOI: 10.1371/journal.pgen.1001063
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional Regulation by CHIP/LDB Complexes

Abstract: It is increasingly clear that transcription factors play versatile roles in turning genes “on” or “off” depending on cellular context via the various transcription complexes they form. This poses a major challenge in unraveling combinatorial transcription complex codes. Here we use the powerful genetics of Drosophila combined with microarray and bioinformatics analyses to tackle this challenge. The nuclear adaptor CHIP/LDB is a major developmental regulator capable of forming tissue-specific transcription comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 71 publications
0
37
0
3
Order By: Relevance
“…Yet, no extra bristles were observed on the scutellum, and some of these flies even exhibited a reduced number of scutellar bristles. 23 these observations indicate that the function of Xbp1 depends on differences between the cellular milieu of the scutum and scutellum. these differences apparently extend beyond the transcription regulation of the CHIP-aP and CHIP-Pnr complexes, allowing for further specificity in directing the differentiation of these tissues.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 71%
See 2 more Smart Citations
“…Yet, no extra bristles were observed on the scutellum, and some of these flies even exhibited a reduced number of scutellar bristles. 23 these observations indicate that the function of Xbp1 depends on differences between the cellular milieu of the scutum and scutellum. these differences apparently extend beyond the transcription regulation of the CHIP-aP and CHIP-Pnr complexes, allowing for further specificity in directing the differentiation of these tissues.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 71%
“…In a recent study, 23 we aimed at analyzing the effect of changing the repertoire of transcription co-factors on the function of two competing transcription complexes that are highly conserved from flies to mice. Both complexes assemble via the co-factor CHIP/LDB (alias CLIM or nLI).…”
Section: Modularity Of Chip/ldb Transcription Complexes Regulates Celmentioning
confidence: 99%
See 1 more Smart Citation
“…SEUSS (SEU) encodes an Arabidopsis protein with a conserved central domain that shares sequence homology with the dimerization domain of the LIMdomain-binding transcriptional coregulators (Franks et al, 2002), which play fundamental roles in animal development (Matthews and Visvader, 2003;Bronstein et al, 2010;Bronstein and Segal, 2011). SEU is widely expressed in Arabidopsis and functions in many developmental processes, including floral organ identity specification, gynoecium, ovule and embryo development, and lateral root initiation (Franks et al, 2002;Pfluger and Zambryski, 2004;Sridhar et al, 2006; .…”
mentioning
confidence: 99%
“…For example, the Drosophila protein called Chip, which can interact with many transcription factors and co-factors (Morcillo et al, 1997;Torigoi et al, 2000;Matthews and Visvader, 2003;Bronstein et al, 2010), has been proposed to play such a role (Dorsett, 1999). In addition, recent studies have revealed critical roles of cohesin and noncoding RNAs in facilitating the communication between enhancers and promoters (Ong and Corces, 2011).…”
Section: Short Distance Vs Long Distance Actionsmentioning
confidence: 99%